Acid fish silage production using snake mackerel (Gempylus serpens) surimi processing wastes. - Calantas, Jana Karla C.
Snake mackerel (Gempylus serpens) surimi processing wastes were converted into acid fish silage products using inorganic acid (sulphuric acid) and organic acid (formic acid). Sulphuric acid at 2.5, 3.5, and 4.5% concentration was used in inorganic acid-treated silages, while formic acid at 2.5, 3.5, and 4.5% concentration was used in organic acid-treated silages. All samples were subjected to chemical analyses including tests for pH, total volatile base-nitrogen (TVB-N), thiobarbituric acid reactive substance (TBARS), degree of hydrolysis (DH), and water activity (aw), and microbial analyses every 4 days until day 16 of ensiling. Proximate analysis was also carried out on day 0 and day 16 samples. The results of the current study showed that the pH and TVB-N values for both sulphuric and formic acid-treated silages were increasing while the TBARS values decreased as the storage period progressed. Results also showed that sulphuric acid silages have a higher degree of hydrolysis. All acid treatments have shown no microbial growth throughout the whole ensiling period. A significant decrease (p<0.5) and lipid content in all treatments of sulphuric and formic acid-treated silages on the final day of storage was also recorded. The results of the current study suggest that sulphuric acid silages were found to have better quality and nutritional composition as compared to formic acid silages. Sulphuric acid at 3.5% concentration has shown the best quality among the acid silages produced.